Decursin from Angelica gigas Nakai Blocks hKv1.5 Channel - Kwak, Yong-Geun; Choi, Bok-Hee; Kim, Dae-Keun; Eun, Jae-Soon (Biomolecules & therapeutics, 2011)
Decursin was purified from Angelica gigas Nakai, and its effects on the human Kv1.5 (hKv1.5) currents were recorded in mouse fibroblasts (Ltk- cells) by whole-cell patch-clamp technique. Decursin inhibited hKv1.5 current in a concentration-dependent manner, with an IC50 value of 2.7 uM at +60 mV. Decursin accelerated the inactivation kinetics of the hKv1.5 channel, and slowed the deactivation kinetics of the hKv1.5 current, resulting in a tail crossover phenomenon. Also, decursin inhibited the hKv1.5 current in a use-dependent manner. These results strongly suggest that decursin is a kind of open-channel blocker of the hKv1.5 channel.